A mudança na poupança era necessária? Evidências a partir de Modelagem Econométrica - Garcia Junior, José Silvério da Cunha (2013)
This work intends to study the behavior of savings accounts and fixed mutual funds balances as a function of the basic interest rate in Brazil, analyzing the impact of a sharp decline on those rates. We evaluate the possible migration of capital from fixed income mutual funds to application on savings accounts that has been used as the rational for the change made by the Brazilian government on the laws that regulate the gains from application on savings accounts. The econometric models used indicated that there was actually a possibility for such migration of capital.